Investigation of the growth mechanism of highly branched silica nanowires grown using in-situ Cu-catalyst loading, and the development of electrochemical anodization synthetic methods specifically targeting solid ionically conducting materials - Boissiere, Jacob Daniel, author; Prieto, Amy, advisor; Finke, Richard, committee member; Rappe, Anthony, committee member; Dandy, David, committee member (Colorado State University. Libraries, 2023)
Gaining a better understanding of the world around us is the fundamental objective of science, with chemistry looking to better understand the processes and applications that occur on a molecular and sub-molecular scale. Developing this better understanding has allowed us to create medicine and computers, begin exploring space and understanding the atom and is a never-ending process of asking questions and testing hypotheses as we work toward an increasingly objective answer. The best that I can hope for, not only in my time in graduate school, but as I move forward in life, is that I have moved this understanding, even in the slightest, in the correct direction. This may be a small impact, but much of the work presented in this dissertation will focus on small things. Two significant research directions will be presented along with work on device and process development for characterization. The first major system that will be discussed is the chemical vapor deposition of highly branched silica nanowires that were grown in a single synthetic step as a result of in-situ Cu-catalyst loading. The second research direction involves the investigation into using electrochemical anodization synthesis as a way to target the formation and discovery of ionically conducting materials. The overall link between these research topics involves the focus on solid inorganic materials, with a broad direction of understanding materials systems, process development and optimization, careful characterization, hypothesis generation, and considerations of potential applications and future directions of the materials and techniques being investigated. Systems of interest could loosely be classified as energy related materials. Both systems provided unique and challenging aspects to understanding the synthetic processes involved as products were formed under highly dynamic environments. Additionally, device and process developments were perused to address systematic variables such as instability of products and improve overall reaction design and therefore reproducibility and significance of results. The first system investigated involved the chemical vapor deposition of silicon-based nanowire products. The initial objective of the project was to investigate the unique structures of highly branched nanowires that were grown through in-situ doping of Cu, and investigate their properties and performance as a potential anode material for use in Li-ion battery devices. The synthetic method used, and the unique structures observed were previously reported by the Prieto research group. The hypothesis was that these products were grown as crystalline Si and being catalytically oxidized due to the presence of Cu and Cu3Si post synthesis. The work presented here disproves this hypothesis, instead proposing that the product is grown as the oxide. Due to this new conclusion, the battery application study was no longer pursued, and investigation instead focused on developing and proposing a new growth hypothesis. This new hypothesis involves the formation of a multi-wire backbone, which is believed to be the first report to directly investigate and explain this phenomenon. The second research direction outlines the motivation, theory, and initial outcomes of attempting to develop a new synthetic methodology for ionically conducting materials through electrochemical anodization. While anodization is itself far from a new synthetic method, it has never been used to synthesize the targeted material systems, nor has it been used to pursue the synthesis of ionically conducting materials generally. Much of the discussion will revolve around the background, motivation, and hypotheses relating to this project. This focus is partially due to the limited success of certain research objectives, but the intention is to hopefully highlight the intrinsic value of the synthetic concept and theory behind it, as well as direct future potential research based on what has been learned. The synthetic results and discussion focus on the anodization synthesis of AgI, the morphologies and crystallographic properties of the materials formed, and insights into the synthetic process. The related systems of CuI and CuxS will also be touched upon, as well as attempts to pursue the synthesis of Na3PS4. Throughout these investigations, a variety of side project and collaborations were worked on, but the one of significance that will be included in the final chapter relates to the development of an air-free sample transfer holder. This was developed to allow the air-free transfer of a surface sensitive material between a glove-box and an X-ray photoelectron spectroscopy instrument. This enables more accurate and meaning data to be collected on samples that could otherwise be modified or compromised through exposure to ambient air before analysis.
Keywords: chemical vapor deposition; electrochemistry; XPS; corrosion; anodization; nanowire